Analisis Strategi Pengembangan Bisnis pada Brand Kerupuk Bambu di Kota Bandung - Retha Damayola; Gunawan Gunawan (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
Bamboo-based processed products are gaining attention as innovative and sustainable local food alternatives. One such product being developed in Bandung is bamboo crackers, which has a unique selling point both in terms of raw materials and locality image. This study aims to explore business development strategies that suit the internal and external conditions of bamboo cracker brands in Bandung. The method used was a qualitative approach through in-depth interviews and participatory observation, as well as SWOT analysis to identify the strategic position of the business. The results showed that strengthening branding, product diversification, and utilizing digital distribution channels are the main strategic steps to encourage business growth. This research provides implementative recommendations for similar businesses in developing local food products that are competitive in national and international markets.